THE RELATIONSHIP BETWEEN TEACHERS’ LEADERSHIP CAPACITY AND OCCUPATIONAL STRESS IN FIRST HIGH SCHOOL OF YUXI, YUNNAN PROVINCE, CHINA - Yang, Shunyi; Ye, Yan (Scholar: Human Sciences, 2022)
The main purpose of this study was to determine the relationships between teachers’ perception of leadership capacity and occupational stress in First High School of Yuxi, Yunnan Province, China. The study was conducted from February until August 2020. This study involved 104 full-time teachers who teach in a selected school as a population. This research used a questionnaire including three parts: Part I was general information, Part II adopted from Pierce’s (2007) based on Lambert (2003) Leadership Capacity School Survey (LCSS), which investigated teachers’ perceptions of their leadership capacity; and Part III adopted from Daniel’s (2014) Teachers’ Occupational Stress Questionnaire (TOSQ), identified teachers’ perceptions on their occupational stress. The collected data was analyzed using descriptive statistics, Mean and Standard Deviation, and Pearson Product Moment Correlation Coefficient. The results showed that teachers’ perception of leadership capacity and occupational stress was high. There was a significant relationship between teachers’ perception of leadership capacities and occupational stress in First High School of Yuxi, Yunnan Province, China.